Impact of creatine supplementation on menopausal women’s body composition, cognition, estrogen, strength, and sleep - Lauren Hall; Sadie Klassen; Jennifer Holbein; John Waters (Journal of the International Society of Sports Nutrition)
Background Despite extensive research on creatine, evidence for use among females is understudied. Understanding the effects of creatine metabolism in peri- and post menopause yields important implications for creatine supplementation regarding performance and health in females. This repeated-measures quasi-experimental study analyzes the effects of Creatine Monohydrate on performance, body composition, cognitive function, estrogen levels, mood and sleep of females in perimenopause and postmenopause.Methods TFifteen females with a mean age of 54 with 5 in perimenopause and 10 in postmenopause participated in this 14 week study. The participants in each group attended 9 sessions over the 14 weeks, following a twice-weekly training schedule based total body strength training program written by the college conditioning coach. The study used a Bod Pod® to analyze body composition, an estradiol spit test to observe estrogen levels, cognitive function assessments, a weekly mood and sleep questionnaire, and an isokinetic dynamometer to examine muscle strength.Results Creatine supplementation led to significant increases in lower body strength across peri- and postmenopausal participants, particularly in the test of the isometric concentric extensor peak torque at 60° for 3 seconds (p < .05). Perimenopausal women demonstrated positive improvements in sleep quality (p = .0181). There were no significant results observed in estradiol levels or non-Humac tests.